Long non-coding RNA CAR10 promotes angiogenesis of lung adenocarcinoma by mediating nuclear LDHA to epigenetically regulate VEGFA/C - Xiaolu Ge; Chao Du; Li Fang; Wei Xu; Juanjuan Xiang; Jiheng Liu; Ming Zhou; Yuejun Chen; Ziyao Wang; Zheng Li (Communications Biology)
Abstract Angiogenesis is a significant character of lung adenocarcinoma (LUAD) and is an important reason leading to high mortality rates of LUAD patients. However, the molecular mechanisms of lncRNAs regulating the angiogenesis in LUAD have not been fully elucidated. Here we show lncRNA chromatin-associated RNA 10 (CAR10) was upregulated in the tumor tissue of patients with LUAD and enhanced tumor metastasis. Mechanistically, CAR10 could bind to Lactate Dehydrogenase A (LDHA) protein to regulate the phosphorylation and acetylation of LDHA and increase the dimerization of LDHA to promote its nuclear translocation, which increased the H3K79 methylation in Vascular Endothelial Growth Factor A (VEGFA) and Vascular Endothelial Growth Factor C (VEGFC) gene interval. CAR10 induced microvascular formation in vivo and in vitro by regulating LDHA-VEGFA/C axis. In addition, MYC and TP53 bonded to the promotor of CAR10 and reverse regulated its expression in LUAD cells. CAR10 regulates post-translational modification of LDHA and increases the H3K79 methylation of VEGFA/VEGFC to promote angiogenesis of LUAD, which is a potential therapeutic target for LUAD.